PENGGUNAAN ANGGARAN DALAM PENILAIAN KINERJA MANAJEMEN - VIALI PANGAU, RUDDY (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to evaluate and to analyze whether the budgeting process and the use of responsibility accounting system is capable to appraise the management performance. The research method is using qualitative method since the researcher is testing a hypothesis. The researcher is using descriptive analysis technique since it describes the researched object as it is. It is found from the result of research that in the implementation the organization structure of PT Nilam Port Terminal Indonesia has clearly shown its responsibility and authority in accordance with the organization structure but it has not made responsibility code center, budgeting system is done by using bottom up budgeting method though it has not included all responsibility center leaders yet, cost account code and the arrangement responsibility report has no separation between controllable and uncontrollable cost. It can be concluded that PT Nilam Port Terminal Indonesia has not implemented the responsibility accounting system. Therefore in order to be able to implement responsibility accounting system, the organization structure of the company should include responsibility code center, cost account code and responsibility report should divide controllable and uncontrollable cost and all leaders of responsibility center participation in budgeting.Keywords: Responsibility Accounting, Performance Evaluation Controllable and Uncontrollable Cost